HBR’s ten must reads on Leadership (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Purpose The purpose of writing this book review is to  make the readers of leadership get an overview of  the classic book from Harvard Business Review  (HBR). The book is basically a compilation of  ten best articles on leadership from the data  bank of HBR. One of the most important  features of the book is that all the articles are  backed by research. Reading on leadership is  required more than ever before in the era of the  COVID-19 pandemic, as it has created new  challenges and opportunities for the global  business environment. This book is a one to be  read in this hard time.
Keywords: basically; challenges; environment